Purificação e caracterização parcial de ATPase de larvas de Zabrotes subfasciatus (Coleóptera: Chrysomelidae: Bruchinae) e modulação fitoterápica de sua atividade - França, Juliana Luzia (2009)
Zabrotes subfasciatus is the most common pest of the stored beans (Phaselous vulgaris). This study was carried out to characterize ATPase from Z. subfasciatus larvae and to investigate its phytotherapy modulation. Larvae extracted from Phaseolus vulgaris were firstly homogenised in extraction buffer, and then centrifuged 45000g for 30min at 4ºC. Supernatant was fractioned with ammonium sulfate, precipitaded fraction on 45-80% saturation was homogenized in reduction ionic strength buffer, centrifuged and the supernatant was applied in ion exchange chromatography on Q-Sepharose. The column was eluted with 200mM NaCl and after that with salt gradient containing 200 to 500mM NaCl. After chromatography, fractions that presented Ca2+/Mg2+-ATPase activity constituted Z. subfasciatus larvae ATPase fraction. The main polypeptide from this fraction showed relative molecular weight similar of the myosin VII. This fraction presented significant K+/EDTA-ATPase activity. Both pyrophosphate and ADP were not hydrolyzed. Tapsgargin, ouabain and azide did not inhibit Ca2+/Mg2+-ATPase activity. Aqueous extracts from leaves of C. ambrosioides, R. officinalis and E. citriodora inhibited Ca2+/Mg2+-ATPase activity, being the last one more effective. These results strongly indicate the presence of myosin in Z. subfasciatus larvae ATPase fraction, considering that it presented high K+/EDTA activity.